GAMBARAN PENGETAHUAN GURU TENTANG PELAKSANAAN ASESMEN DI TAMAN KANAK-KANAK SE KECAMATAN BUKIT RAYA KOTA PEKANBARU - Nurul Fitri, Dwi Anisak Nurul Fitri Anisak; Novianti, Ria Novianti Ria; ', Zulkifli N Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Knowledge of the assessment is very important in conducting assessments of early childhood development in order gather information and assess the needs and potential of children, it also used to ability and weaknesses of the child. Educators backgrounds S1 must have pedagogic competence in carrying out the assessment, and therefore the need for teachers to have a broad knowledge of the assessment. But the phenomenon that there are still shortcomings in terms of teacher knowledge and assessment of the implementation of early childhood development. Therefore, this study was conducted in order to describe how the description of kindergarten teacher’s assessment knowledge in bukit raya distridct, pekanbaru.. The results show: 1) Teacher's assessment knowledge on the implementation of the principle of assessment is low when compared with other aspects that are included in the category of less well with the percentage of 58.05%. 2) The overall indicator teacher's assessment knowledge in kindergarten District Bukit Raya Pekanbaru are in low category with a total percentage of 56-65%. Based on finding the solution to the teacher’s ass knowledge are construction through supervision from kindergarten headmaster and conducting ass training for teacher’s to increase assessment knowledge and implementation.Keywords: Assessment, knowledge, teacher’s, kindergarten.